Konfigurasi Filantropi Islam Era Digital: Studi Peran Sedekah Pada Aplikasi Media Sosial Youtube - miladi, Nuril; Noviyanti, Ririn (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
Digitization brings various new features that humans can use to interact with each other. The spread of social media is often used as a job by its users, various ways are used to be able to monetize the content uploaded on the channel. Currently, YouTube is the most visited channel. Some creators have succeeded in developing their channels by integrating Islamic philanthropy into their content. This research aims to determine the role of Islamic philanthropic content on the content components. This study uses a qualitative-content analysis method to map a variety of positive content containing philanthropy on YouTube Indonesia. Content analysis is done by looking at digital content and its impact. The results of this study indicate that charity with philanthropic content can be used as a source of income, lighten the target economy on content, and has the potential to enlarge the philanthropic ecosystem in real life.